From Minos to Midas : Ancient Cloth Production in the Aegean and in Anatolia - Burke, Brendan (Ancient textiles series, 2010)
Textile production was of greater value and importance to people in the past than any other social craft activity: everyone depended on cloth. As with other craft goods, such as pottery, metal objects, or ivory carving, the large-scale production and exchange of textiles required specialization and some degree of centralization. This book takes an explicitly economic approach to textile production, focusing on regional centers, most often referred to as palaces, to understand the means by which states in the Aegean and Anatolia financed themselves through cloth industries. From this we can loo